2021
DOI: 10.1038/s41598-021-92331-8
|View full text |Cite
|
Sign up to set email alerts
|

The LIM domain protein nTRIP6 modulates the dynamics of myogenic differentiation

Abstract: The process of myogenesis which operates during skeletal muscle regeneration involves the activation of muscle stem cells, the so-called satellite cells. These then give rise to proliferating progenitors, the myoblasts which subsequently exit the cell cycle and differentiate into committed precursors, the myocytes. Ultimately, the fusion of myocytes leads to myofiber formation. Here we reveal a role for the transcriptional co-regulator nTRIP6, the nuclear isoform of the LIM-domain protein TRIP6, in the tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Thus, the transient increase in nTRIP6 expression occurs via increased translation initiation at AUG2. We have previously shown that nTRIP6 represses premature myoblast differentiation, allowing proper myocyte differentiation and fusion at later stages (Norizadeh Abbariki et al, 2021). Accordingly, treatment of C2C12 myoblasts with the AUG2 PNA accelerated the expression of Myog mRNA, used as an indicator of early myocytic differentiation (Edmondson & Olson, 1989) and delayed the expression of Tnni2, a late differentiation gene (Lin et al, 1994), as compared to untreated cells or cells treated with the control PNA (Fig 1F,G).…”
Section: Ntrip6 Is Generated By Alternative Translation At An Interna...mentioning
confidence: 64%
See 4 more Smart Citations
“…Thus, the transient increase in nTRIP6 expression occurs via increased translation initiation at AUG2. We have previously shown that nTRIP6 represses premature myoblast differentiation, allowing proper myocyte differentiation and fusion at later stages (Norizadeh Abbariki et al, 2021). Accordingly, treatment of C2C12 myoblasts with the AUG2 PNA accelerated the expression of Myog mRNA, used as an indicator of early myocytic differentiation (Edmondson & Olson, 1989) and delayed the expression of Tnni2, a late differentiation gene (Lin et al, 1994), as compared to untreated cells or cells treated with the control PNA (Fig 1F,G).…”
Section: Ntrip6 Is Generated By Alternative Translation At An Interna...mentioning
confidence: 64%
“…Our previous observation that the levels of nTRIP6 transiently increased during C2C12 myoblast differentiation whereas those of TRIP6 did not vary (Norizadeh Abbariki et al, 2021) suggests an increased translation at AUG2. To address this question, we used the AUG2 and the control PNAs fused to a cell-penetrating peptide 15,16 in a C2C12 differentiation assay.…”
Section: Ntrip6 Is Generated By Alternative Translation At An Interna...mentioning
confidence: 94%
See 3 more Smart Citations